On civil-law aspects of criminal-law confiscation from the point of view of the executive proceedings - Nikanava, Nataliya N. (Journal of the Belarusian State University. Law, 2019)
The regulation of criminal-law confiscation by acts of different brunches caused the almost complete absence of comprehensive fundamental research on the issues of criminal-law confiscation, the presence of numerous lacunes and collisions in legal regulation, the discrepancy between doctrinal and practical understanding of confiscation. Confiscation was considered as the basis of origin of the right of state property and the basis for the termination of the right of private property in the works of the civilists. In the works on criminal and criminal-executive law, civil-law aspects of criminal-law confiscation usually are not regarded, excluding “Confiscation of property: past, present, future” by A. А. Propostin. Analysis of legislation and practice of enforcement proceedings led the author to conclude that there are three substantial problems in the execution of writs for seizure: the determination of objects (property) that can be confiscated; the determination of the moment of termination of the right of private property and the moment of the origin of state property; succession as the result of confiscation. The author comes to the conclusion that only the asserts that belong to the debtor on the right of property are subject to seizure, that legislation changes that spread the confiscation to other types of assets are required, that the debtor’s ownership of the confiscated property is terminated upon the judgment goes in effect, that confiscation is the basis for a singular succession: a number of obligations of the convicted person passes to the state, that according to the criterion of the earlier existence of the right of property, confiscation of the property is the derivative basis of origin of the right of property, consequently the previously existing restrictions/encumbrances remain, unless otherwise provided.